Inoculation of rhizobia increases lima bean (Phaseolus lunatus) yield in soils from Piauí and Ceará states, Brazil - do Nascimento Costa, Claudyanne; Lopes Antunes, Jadson Emanuel; Celis de Almeida Lopes, Angela; Santiago de Freitas, Ana Dolores; Ferreira Araujo, Ademir Sérgio (Revista Ceres, 2025)
The inoculation of rhizobia in lima bean can increase its yield and contribute to smallholder farms. In this study, the potential of rhizobia in increasing the lima bean yield was evaluated in two regions from Piaui and Ceará states. The experiments were conducted in field comparing three rhizobia strains (UFPI32, UFPI38, UFPI59), one strain of reference to Phaseolus vulgaris (CIAT899) and two controls (with and without nitrogen). The parameters of nodulation, N accumulation and yield varied between treatments and locations. The nodule biomasses were higher in UFPI59 and UFPI32 (Piauí), and CIAT899 and UFPI32 (Ceará). The highest values of nodule size were found in treatments UFPI59 in both locations. Lima bean presented highest values of leaf N in UFPI59 and CIAT899. The highest values of grain yield were found in the treatment UFPI59 as compared to CIAT899 and the controls. The results confirmed the potential of UFPI59 in promoting nodulation, N accumulation, plant growth and yield of lima bean in both locations.